THE EDUCATIONAL INFORMATION ENVIRONMENT AS A CONDITION FOR THE SUCCESS OF A LINGUISTIC PERSONALITY FORMATION - Kokarieva, Anzhelika; Pryshupa, Yuliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article reveals the features of the modern educational information environment for the success of linguistic personality formation. The authors of the article prove the importance of integrating the educational and information environment into the pedagogical process, where all component processes are exposed to personality formation, influence the professional formation of the future specialist and play a significant role in the formation of linguistic personality. The purpose of the article is the theoretical substantiation and empirical study of the level of the educational and information environment influence on language personality formation success in higher education institutions. The research tasks are focused on the scientific substantiation of the concepts of "educational and information environment" and "linguistic personality"; identification of factors in the formation of linguistic identity success; analysis and interpretation of research results regarding the influence of the educational and information environment on the linguistic personality formation. The results of the study prove that the educational and information environment is a combination of the latest information technologies and modern pedagogical developments, which should lead to the maximum effect of a sufficient educational process. Various roles of the educational and information environment in the educational process are considered. Where the specified environment can be both a means of supporting the educational process and a means of implementing blended learning. In our study, the educational and informational environment is considered in the paradigm of the distance learning organization. The classification of the levels of the information and educational space and the requirements for distance learning is revealed. The research proposes and justifies the choice of Internet technologies to create a new level of education and information environment. Research also proved the establishment of contact between all participants of the educational process; sample settings are necessary when the students' load of educational material is determined. In the course of questionnaires and surveys of participants in the educational and pedagogical process of technical universities, the peculiarities of the organization of professional training of future specialists in the conditions of distance learning, their influence on the success of language personality formation, and motivation to study were established. Conclusions. Summarizing the results of the study on the influence of the educational and information environment on linguistic personality formation, the authors substantiate the need for learning a foreign language. On the basis of productive educational activities, the development of a foreign language is a component of forming a linguistic personality. It is noted that the use of Internet resources creates conditions for the implementation of an individual and differentiated approach to foreign language learning as well as forms the ability to work, analyse and evaluate information. The article reveals the advantages of implementing an educational and information environment during distance learning of foreign languages and emphasizes that despite all the problems of introducing the specified form of education into the educational process, the educational and information environment helped both teachers and students to discover new opportunities, to get a new positive experience of working with Internet platforms and digital tools, and also contributed to the success of linguistic personality formation